High‐Z Metal–Organic Frameworks for X‐ray Radiation‐Based Cancer Theranostics. Issue 10 (15th December 2020) - Neufeld, Megan J.; Lutzke, Alec; Pratx, Guillem; Sun, Conroy
Abstract: X‐ray radiation is commonly employed in clinical practice for diagnostic and therapeutic applications. Over the past decade, developments in nanotechnology have led to the use of high‐ Z elements as the basis for innovative new treatment platforms that enhance the clinical efficacy of X‐ray radiation. Nanoscale metal–frameworks (nMOFs) are coordination networks containing organic ligands that have attracted attention as therapeutic platforms in oncology and other areas of medicine. In cancer therapy, X‐ray activated, high‐ Z nMOFs have demonstrated potential as radiosensitizers that increase local radiation dose deposition and generation of reactive oxygen species (ROS). This minireview summarizes current research on high‐ Z nMOFs in cancer theranostics and discusses factors that may influence future clinical application. Abstract : High‐ Z nanoscale metal–organic frameworks (nMOFs) have attracted attention in oncology as X‐ray contrast agents and radiosensitizers that enhance the effect of radiation therapy.